Analisis Beban Kerja Terhadap Kinerja di Approach Control Unit Makassar Air Traffic Service Centre - Yunita Kireina; Rini Sadiatmi; Mohammad Faizal; Oke Hendra (Politeknik Penerbangan Indonesia Curug, 2022)
The process of guiding air traffic is not only for planes in the air but also for landing, take-off and setting up the plane to the parking stand. Analysis of the problem found a very high workload that had an impact on ATC performance, where an ATC every day had to be responsible for guiding and supervising hundreds or even thousands of planes carrying thousands to millions of people on planes. The purpose of the study was to determine how much influence the workload had on the performance of ATC personnel at the Approach Control Unit Makassar Air Traffic Service Center. The research method uses quantitative methods with a correlative approach. The result of this research is that there is a strong negative relationship between workload and the performance of ATC Approach Control Unit Makassar Air Traffic Service Center. The conclusion of the study shows that there is a fairly strong relationship between workload on ATC APP performance in MATSC and workload has a significant contribution to ATC performance.